USE OF STYLISTIC STYLES IN ARTISTIC TEXT - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
linguistic features of the artistic style in this article, phonetic, lexicphraseological, grammatical features and special expression image means, application of words, illuminated by the example of works of art.